Assessing the Hybrid Effects of Neutral and Niche Processes on Gut Microbiome Influenced by HIV Infection - Yin, Guanshu; Xia, Yao (Frontiers in Microbiology, 2019)
That both stochastic neutral and deterministic niche forces are in effect in shaping the community assembly and diversity maintenance is becoming an increasingly important consensus. However, assessing the effects of disease on the balance between the two forces in the human microbiome has not been explored to the best of our knowledge. In this article, we applied a hybrid model to address this issue by analyzing the potential effect of HIV infection on the human gut microbiome and adopted a further step of multimodality testing to improve the interpretation of their model. Our study revealed that although niche process is the dominant force in shaping human gut microbial communities, niche process- and neutral process-driven taxa could coexist in the same microbiome, confirming the notion of their joint responsibility. However, we failed to detect the effect of HIV infection in changing the balance. This suggests that the rule governing community assembly and diversity maintenance may be changed by the disturbance from HIV infection-caused dysbiosis. Although we admit that the general question of disease effect on community assembly and diversity maintenance may still be an open question, our study presents the first piece of evidence to reject the significant influence of diseases.